An Investigation of Co-Integration and Causality between Trade Openness and Government Size in Turkey - Aydogus, Ismail; Topcu, Mert (International Journal of Economics and Financial Issues, 2013)
Validity of globalization brings out the question of whether greater openness is a booster reason to have a bigger government. This issue has been started to be discussed in relevant literature since the late 1970s. In this context, the purpose of this study is to examine the linkage between trade openness and the size of the government in Turkey over the period 1974-2011. Using residual based co-integration approach, we fail to find an evidence of a long run relationship. In addition, we do not provide causal support of compensation hypothesis in Turkish economy. Keywords: Government size; trade openness; Turkish economy JEL Classifications: F10; H10